Evaluation of Ferric and Ferrous Iron Therapies in Women with Iron Deficiency Anaemia - Ilhami Berber; Halit Diri; Mehmet Ali Erkurt; Ismet Aydogdu; Emin Kaya; Irfan Kuku (Advances in Hematology)
Introduction. Different ferric and ferrous iron preparations can be used as oral iron supplements. Our aim was to compare the effects of oral ferric and ferrous iron therapies in women with iron deficiency anaemia. Methods. The present study included 104 women diagnosed with iron deficiency anaemia after evaluation. In the evaluations performed to detect the aetiology underlying the iron deficiency anaemia, it was found and treated. After the detection of the iron deficiency anaemia aetiology and treatment of the underlying aetiology, the ferric group consisted of 30 patients treated with oral ferric protein succinylate tablets (2 × 40 mg elemental iron/day), and the second group consisted of 34 patients treated with oral ferrous glycine sulphate tablets (2 × 40 mg elemental iron/day) for three months. In all patients, the following laboratory evaluations were performed before beginning treatment and after treatment. Results. The mean haemoglobin and haematocrit increases were 0.95 g/dL and 2.62% in the ferric group, while they were 2.25 g/dL and 5.91% in the ferrous group, respectively. A significant difference was found between the groups regarding the increase in haemoglobin and haematocrit values (P<0.05). Conclusion. Data are submitted on the good tolerability, higher efficacy, and lower cost of the ferrous preparation used in our study.